2011
DOI: 10.1523/jneurosci.1537-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Constant Darkness Induces IL-6-Dependent Depression-Like Behavior through the NF- B Signaling Pathway

Abstract: Substantial experimental evidence indicates a major role for the circadian system in mood disorders. Additionally, proinflammatory cytokines have been proposed to be involved in the pathogenesis of depression. However, the molecular elements determining the functional interplay between these two systems in depression have not been described as yet. Here we investigate whether long-term light deprivation in the constant darkness (DD) paradigm affects depression-like behavior in mice and concomitantly modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(140 citation statements)
references
References 58 publications
(73 reference statements)
7
127
0
6
Order By: Relevance
“…This evidence builds upon a previously study that demonstrated an antidepressant-like response to acute stress in constitutive IL-6 knockouts and suggests that leukocyte-derived sources of IL-6 may be critical in mediating these behavioral effects (34). Our results are interesting in light of recent studies showing that social defeat stress induces downstream inflammatory signaling pathways, such as NFkB (26,(35)(36)(37), and increases monocyte trafficking (29) throughout a number of CNS structures known to control depression and anxiety behavior. It will be important for future studies to define the brain regions and molecular pathways induced by stress-responsive IL-6 from leukocytes that mediate adverse behavioral responses to chronic stress.…”
Section: Significancesupporting
confidence: 84%
See 1 more Smart Citation
“…This evidence builds upon a previously study that demonstrated an antidepressant-like response to acute stress in constitutive IL-6 knockouts and suggests that leukocyte-derived sources of IL-6 may be critical in mediating these behavioral effects (34). Our results are interesting in light of recent studies showing that social defeat stress induces downstream inflammatory signaling pathways, such as NFkB (26,(35)(36)(37), and increases monocyte trafficking (29) throughout a number of CNS structures known to control depression and anxiety behavior. It will be important for future studies to define the brain regions and molecular pathways induced by stress-responsive IL-6 from leukocytes that mediate adverse behavioral responses to chronic stress.…”
Section: Significancesupporting
confidence: 84%
“…Both in vivo and ex vivo IL-6 levels in response to stimulation were the strongest predictor of the behavioral response to a subsequent social stress. Although previous studies have identified elevated serum IL-6 and circulating leukocytes in stress disorders, this generally followed either depression diagnosis in humans (4,25) or controlled stress exposure in rodents (26,27). To our knowledge, this is the first study to show that the IL-6 response before social stress exposure can predict individual differences in vulnerability to a subsequent social stressor.…”
Section: Significancementioning
confidence: 87%
“…It has previously been shown that p53 mutant mice lacking functional CRY proteins are more susceptible to TNF-α-initiated apoptosis through NF-κB activation (39). Monje et al had reported that depression like behavior in mice induced by constant darkness is associated with increased levels of IL-6 in plasma and hippocampus mediated through NF-κB signaling pathway (40). Interestingly, NF-κB has been shown to play a role in metabolic adaptation both in normal and also in cancer cells by regulation of mitochondrial oxidative phosphorylation (41), and the current finding will suggest an additional CRY-NF-κB-mediated pathway in metabolic adaptation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, long-term light deprivation in the constant darkness paradigm induces elevated levels of IL-6 and IL1-R1 (interleukin 1 receptor, type I) in the hippocampus through the NF-κB signaling pathway, known to play a vital role in the cellular expression of pro-inflammatory genes [47] . Moreover, the expression of pro-inflammatory cytokines is induced by a high oxidative-stress status.…”
Section: Can the Brain Produce Cytokines?mentioning
confidence: 99%